Representasi Kelompok Minoritas Disabilitas Netra Dalam Film Dokumenter The Unseen Words - Dinda Meutia Anggraeni; Filosa Gita Sukmono (UMSU, 2019)
This study explains about a minority representation of people with blind disability in Indonesia by using a documentary movie entitled ‘The Unseen Words'. Simply, the awareness of the disabled people is basically, these disable people are including the people who have the same equality with others. However, in reality, these disability people are still far from equality even they became objects of alienation and discrimination. The method used to analyze this movie was semiotic analysis with Roland Barthes approach. This study found some results as follows: Firstly, the minority representation of people with blind disability was portrayed as the people who lived in the circle of poverty and alienation, secondly, the minority representation of these blind people was portrayed as a discrimination object, thirdly the minority representation of these blind people was portrayed as objects who were not concerned about accessibility and public services, and lastly, the minority representation of these blind people was also portrayed as a symbol of suffering. Keywords: representation, minority, people with blind disability, movie